Analysis of the factors of planned and emergent use of cardiopulmonary bypass assistance in beating heart coronary artery bypass grafting operations - Ie. A. Nastenko; O. O. Zhurba; O. K. Nosovets; Yu. V. Shardukova; A. V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
With the clinical material of 3958 beating heart CABG, made in 2009–2013, the factors, associated with use of planned and emergent cardiopulmonary bypass (CPB) assistance were considered. It was shown, that the structures of the significant factors in both cases are similar. The factors that may cause the erroneous decisions concerning to operation tactic were established. The necessity of development of computer decision support systems to minimize the risk of emergent use of CPB assistance use was shown.